Culture And Financial Management Of Nepalese And Japanese Married Couples Living In Japan - Sapkota, Nisha; Dangol, Jeetendra (Nepalese Journal of Management and Technology, 2024)
The study aims to analyze the difference in culture and management of financial activities among married couples of Nepal and Japan using questionnaire survey methods. Convenience sampling method was used in survey with 120 each Nepalese and Japanese couples’ couple. First aspect was handling finance this includes sharing about finance and credit management of Japanese and Nepalese couples. Second aspect was financial knowledge which includes financial literacy. Third aspect was happy marriage which includes financial satisfaction and commitment and enjoyable time spend together. Demographic factors like number of years married, age, education, income level, type of family, were also consider to analyze the culture and financial management activities among Japanese and Nepalese couples. Using logistic regression method, the study finds Japanese couples management of finance is done by women but in Nepal both husband and wife manage finance. Nepalese couples’ employment is higher than of Japanese. The Nepalese and Japanese couples preferred to have joint accounts. Japanese couples have a good knowledge of managing credit than Nepalese.